Faktor-Faktor yang Berhubungan dengan Penggunaan Metode Kontrasepsi angka Panjang di Kecamatan Pemenang Kabupaten Lombok Utara NTB - Parmiwati; Endy Bebasari Ardhana Putri; Arista Kusuma Wardani,; Nurhidayah (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: The number of couples of childbearing age in North Lombok Regency is currently 47,211 and 31,824 (67.4%) are active family planning participants. There are 30.75% of couples of childbearing age who use long-term contraceptive methods and 18.31% of women in the sub-district use long-term contraceptive methods, this is lower than the national target of 23.5%. Objective: To determine the factors associated with the use of long-term contraceptive methods in Selamat District, North Lombok Regency.  Method: This is a quantitative study with a crosssectional research design. The research was conducted in 2022 in North Lombok. The population of all couples of childbearing age who are > 35 years old and who are already family planning participants in Selamat District is 1,761 PUS. The sample size is 10% of the total population of 177 couples of childbearing age. The sample uses random sampling and uses a questionnaire instrument. Data analysis used the Chi-Square test with a significance level of 0.05.  Results: Knowledge of female reproductive couples in the good category was 51 people (28.8%), the poor category was 108 people (61%) and the poor category was 18 people (10.2%). Husband support was in the good category as many as 24 people (13.6%), in the less good category as many as 140 people (79.1%) and in the bad category as many as 13 people (7.3%). After carrying out the Chi-Square test, the results obtained were significant for knowledge, husband's support and the role of Family Planning Field Officers ρ = 0.000 < 0.05. Conclusion: There is a relationship between maternal knowledge, husband's support, and the role of Family Planning Field Officers with the use of Long-Term Contraceptive Methods in Selamat District, North Lombok Regency.